Between tradition and modernity: the relationship among healers and medicinal plants in an urban center in southern Brazil. - da Silva, Camila Fabiana; Zank, Sofia (Ethnobotany Research and Applications, 2022)
Background: Blessing (or benzedura) is a traditional health practice present in both rural and urban areas of Brazil. Several ethnobotanical studies demonstrate that practitioners have a vast knowledge of medicinal plants; however, it is still necessary to expand research to include the importance of the practice and the ways knowledge is transmitted when facing modernity. Thus, this study was conducted in an urban region of Florianopolis (SC) where we sought to investigate the diseases treated by blessings, the plants used in this practice, and the process of cultural transmission. Methods: We conducted interviews with eleven healers from the eastern region of Florianopolis. Information was collected through semi-structured protocols with a free list of plants, and the botanical collection and identification of mentioned plants. Data was analyzed using descriptive statistics. Results: A total of 34 types of diseases and ailments that are treated through blessings were cited. For the treatment and cure of these ailments, the use of 24 species of medicinal plants was recorded, the most cited were Ruta graveolens (6 citations), Rosmarinus officinalis (3) and Petiveria alliacea (3). In terms of knowledge transmission, most respondents (46%) learned in childhood, 36% learned in adulthood through course, and 18% learned in adolescence. During the interviews, we noticed that new ways of transmitting knowledge are emerging, where courses and mobile applications are gaining importance. Conclusions: The practice of blessing continues to play an important role in the health of communities in the eastern region of Santa Catarina Island, and it is undergoing modernizing adaptations. It is important that future studies investigate the effect of technologies on this practice and the possible implications for the resilience or vulnerability of these health systems. Keywords: Blessings, ethnobotany, health practices, local ecological knowledge, medicinal plants.